Glacial and Periglacial Landscapes of the Serra da Estrela - Vieira, Gonçalo; Nieuwendam, Alexandre (Springer, 2020)
The Serra da Estrela is a granite-dominated plateau mountain located in Central Portugal, reaching an elevation of 1993 m. Its position in the western part of the Iberian Central System, elongated morphology in an SW–NE direction, generates an important barrier to the moist Atlantic air masses when they move into Iberia’s interior. This orographic rainfall effect is important today, as it was in the Pleistocene, generating high amounts of precipitation, which in the Pleistocene were key for glacier development. The presence of a plateau above 1400 m and a regional equilibrium line altitude at about 1650 m were key for the development of a plateau ice field, very sensitive to small climate oscillations, but responsible for the development of several radiating valley glaciers. The effects of this glacial system on the landscape were remarkable, with the development of numerous landforms and deposits, which are rare in such a geographical setting. The main geomorphological highlights are the erosional landscape of the western plateau, as well as the glaciated section of the Zêzere valley, which under the action of 11.3 km long and over 340 m thick glacier, developed impressive glacial features. The periglacial action occurred mainly in the non-glaciated parts of the plateaus and valley slopes and testify the significance of frost action all over the mountain, with the presence of permafrost at the plateaus and sites above about 1300 m. info:eu-repo/semantics/publishedVersion